Gamification of E-Commerce Simulation: Improving Understanding of Digital Marketing and Entrepreneurship Concepts in Economic Learning - Bustanul Aulia (CV Naskah Aceh, 2025)
Conventional economics learning, particularly on marketing and entrepreneurship, is still predominantly theoretical through lectures and textbooks. This causes core concepts such as digital marketing strategies, pricing, and business financial analysis to be abstract and difficult for students to understand in depth. This study uses a qualitative approach with a library research type . The data sources that will form the foundation of this research are entirely secondary data, which are classified into three main categories. The results of the study indicate that: 1). From Theory to Practice: Uncovering Curriculum Rigidity Through Digital Selling Experience Simulation is that the digital selling experience simulation successfully transforms economics learning from a rigid theoretical approach to a contextual experience. 2). Game Mechanism: Designing a Learning Cycle from Planning to Financial Statement Analysis is that mapping structured game mechanisms that form a comprehensive learning cycle. Students go through three main phases: business planning (market research, COGS calculation), execution (creating an online store, digital marketing strategy), and evaluation (sales data analysis, preparation of profit and loss statements). The integration of gamification elements such as a points system, badges, and leaderboards creates a holistic learning process that integrates marketing, operational, and financial aspects. Impact and Reflection: Measuring the Improvement of Digital Economic Literacy and Students' Entrepreneurial Spirit is that the implementation of e-commerce simulation gamification produces a multidimensional impact on improving digital economic literacy and strengthening students' entrepreneurial spirit. There was a significant increase in conceptual understanding where students not only understand economic terminology but are also able to apply it in business decision-making.